Pengembangan Media Pembelajaran Berbasis Aplikasi Padlet Pada Materi Inflasi Kelas XI SMA Negeri 6 Banjarmasin - Fitri, Annisa Norhayati; Rahmattullah, Muhammad; Nor, Baseran; Ratumbuysang, Monry Fraick Nicky Gillian (Jurnal Pendidikan Ekonomi (JUPE), 2024)
The learning media development research aims to determine the feasibility of padlet media and student learning outcomes after using padlet media in inflation material for class XI IPS SMA 6 Banjarmasin. This research is a Research and Development study with Thiagarajan's 4-D development model modified to 3D. The development steps carried out by researchers are Definition stage, Design stage and Development stage, with data collection techniques using interviews as initial data, questionnaires and test questions. Validation is carried out by media and material experts. The media developed tested on 35 students of class XI IPS 1 SMA 6 Negeri Banjarmasin using a quasi-experimental method without any comparison class. The research results obtained through the definition, design and development process show that Padlet learning media is very suitable for use in economic learning with media expert validation results and material expert validation results in the very feasible category. The results of the t-test show that student learning outcomes have increased in the average posttest score compared to the average score at the pretest. And the score gain normalization test results it is in the high category.